Karyotype features based on diploid number and sex chromosome system of Steatoda grossa (Araneae: Theridiidae) from Turkey - Zübeyde Kumbıçak (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Inthis study, karyotypic investigation of Steatodagrossa belonging to the family, Theridiidae was carried out to contributecytogenetic relationships of the family. A standard air-drying method was usedto obtain chromosome slides including three main steps as hypotonisation,fixation and staining. As a result, the diploid number and sex chromosomesystem was determined as 2n♂=22 (X1X2). All chromosomeswere telocentric and gradually decreased in size. Sex chromosomes werepositively heteropycnotic in the stages of meiosis I, and isopycnotic inmeiosis II. The results showed the similarity with the previous investigationsobtained from different populations.